Advanced methods for activated carbon from agriculture wastes; a comprehensive review - Yunus, Zalilah Murni; G., Yashni; Al-Gheethi, Adel; Othman, Norzila; Hamdan, Rafidah; Ruslan, Nurun Najwa (Taylor and Francis, 2020)
The rapid increase in various industries and the subsequent contamination of water bodies by heavy metals caused water stress circumstances globally. The adsorption is among the effective methods which is used for removing heavy metals from the water bodies. Moreover, the adsorption treatment of wastewater by activated carbon (AC) from bio-waste is getting recognition among researchers due to cost-effective. Therefore the current paper aimed to review the adsorption by activated carbon from agro waste, preparation method of AC and adsorption mechanism. The factors affecting the adsorption, adsorption isotherm and kinetics of adsorption were also reviewed. It is appeared from the reviewed papers that the AC from agro waste exhibited high efficiency in removing heavy metals from different wastewater. Moreover, the metal-adsorbed adsorbent desorption through dilute acids are HCl, HNO3, NaOH, KOH, H2SO4, NaNO3, EDTA and Na-citrate. Therefore, the suitable eluting chemicals to the adsorbent and adsorbate must be selected in order to enable maximum recovering percentage.